Studies of fungi associated with Tomicus piniperda L. in Finland - Silva, Ximena (Helsingfors universitet, 2011)
The Scots pine bark beetle, Tomicus piniperda is a secondary colonizer of pine and other conifers. It is a native species from Europe and Asia that was recently introduced in North America. Although it is necessary to understand this insect's interactions with other organisms, few studies have focussed on its fungal associates. This study focused on the effect of latitude in the occurrence of fungi associated with T. piniperda. T. piniperda were collected from Pinus sylvestris in Northern (Rovaniemi) and Southern (Hyytiala) Finland. Both endo- and epi- mycota were isolated. The fungi were identified using a combination of morphological features and molecular data. The results revealed a great diversity of fungi species associated with T. piniperda, with a total of 3073 isolates representing 23 species. The most frequently isolated fungi in the bark beetles from Northern Finland were Beauvaria bassiana, Kuraishia sp. and Penicillium sp. whereas P. brevicompactum and Mortierella sp. were mostly observed in the South. Ophiostoma canum and O. minus were also observed. The number of isolates per insect in the north was 2.83 epi- and 2.38 for endo-mycota fungus. In the south, the number of isolates per insect was 4.1 for epi- and 3.5 for endo-mycota. Statistical analysis indicated that there was significant differences in fungal populations associated with the beetles in Southern and Northern Finland. There was however no significant difference between the epi- and endo-mycota fungal populations. The highest richness and diversity of the fungal species was observed in the South. However, the overall fungal diversity index analysis revealed that the mycobiota was undersampled. Pystynävertäjä (Tomicus piniperda L) on mäntyjen ja muiden havupuiden tuholainen. Se kuuluu Euraasian alkuperäiseen lajistoon ja on hiljattain levinnyt myös Pohjois-Amerikkaan. Huolimatta pystynävertäjän yleisyydestä ja merkityksestä, hyönteisen sieniosakkaat tunnetaan huonosti. Tässä työssä tutkittiin maantieteellisen sijainnin vaikutusta ...